Surgery-induced changes in erythrocyte and plasma lipid peroxidation, enzymatic and non-enzymatic antioxidants of female rats: Protective role of heparin and pentoxifylline - Simsek, Halil; Durmus, Ali Said; Yildiz, Hamit; Ozcelik, Mehtap (Universidade Federal do Rio Grande do Sul, 2018)
Background: Intra abdominal adhesions are a complication that occurs after many abdominal surgical procedures, especially gynecological operations. These complications occur by irritating the peritoneum due to such circumstances as infection or surgical trauma, and are considered a pathological part of the healing process of peritoneal injury. It manifests itself with symptoms such as pain, intestinal or urethral obstruction and abdominal abscesses. Oxidative stress due to adhesions plays an important role on adhesion formation. In addition to many researches done at the point of prevention of adhesion and decreasing stress parameters, in this study, it was planned to determine the effect of Heparin (H) and Pentoxifylline (PTX) on malondialdehyde (MDA) and some antioxidant values. Materials, Methods & Results: This study was performed on rats and thirty-seven female Sprague-Dawley rats were randomized into four groups. The first group was sham (Sh) group (n = 7) and laparotomy was performed and 2 mL of 0.9 % NaCl was applied. For all other rats (n = 30) the small intestine was withdrawn and the uterus was uncovered and the anti mesenteric surfaces of the left uterine horn and left abdominal wall were superficially tilted until slight bleeding was seen. Lesion areas have been covered. Two mL 0.9 % NaCl to control (C) group (n = 10), 500 IU heparin to group H, and 25 mg / kg Pentoxifylline to group PTX (n = 10) have been given and then the abdominal incision was closed. The adhesion score of group Sh was found to be more important than C and PTX groups (P < 0.05). The adhesion score of group C was determined to be more significant than group H (P < 0.05). In group Sh, erythrocyte reduced glutathione (GSH) levels were found to be more significant (P < 0.01) than C, H and PTX groups whereas it was found that group C was more significant than group H (P < 0.01). In group Sh, glutathione peroxidase (GSH-Px) activity was found to be more significant (P < 0.05) than H and PTX groups, while MDA level was found to be lower and more significant (P < 0.01) than group C. In addition, group C was found to be higher and more significant (P < 0.01) than group H. Plasma vitamin E levels in Sh, H and PTX groups were found to be higher and more significant (P < 0.01) than group C. It is also observed that MDA levels in group C are higher and more significant (P < 0.01) than all groups. Nitric oxide (NO) level in Sh group was found to be lower and more significant (P < 0.05) than the other groups whereas it is determined that NO level in H group is higher and more significant (P < 0.05) than group C. Activites of erythrocyte catalase (CAT) and superoxide dismutase (SOD), the levels of plasma vitamin A and ?-carotene were not important in all groups. Discussion: Intra abdominal adhesions that occur due to operations performed in the abdominal region still remain as a major problem. This adhesion brings certain problems with itself. Various applications have been made to reduce these problems. In this study, it was observed that inhibition of heparin and pentoxifylline adhesions contributed to the reduction of MDA levels and the reduction of oxidative damage due to the increase in levels of Vitamin E, GSH, GSH-Px and NO levels. In conclusion, it is suggested that heparin and pentoxifylline should be used to prevent adhesions due to abdominal operations and to reduce oxidative damage. © 2018 Universidade Federal do Rio Grande do Sul. All rights reserved.
Keywords: Adhesion; Antioxidants; Heparin; MDA; Pentoxifylline; Rat